2015
DOI: 10.1007/s10567-015-0194-6
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Intensive Longitudinal Methods to Investigate Change: Stimulating the Field of Applied Family Research

Abstract: The use of intensive longitudinal methods (ILM)—rapid in situ assessment at micro timescales—can be overlaid on RCTs and other study designs in applied family research. Especially when done as part of a multiple timescale design—in bursts over macro timescales, ILM can advance the study of the mechanisms and effects of family interventions and processes of family change. ILM confers measurement benefits in accurately assessing momentary and variable experiences and captures fine-grained dynamic pictures of tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 100 publications
(130 reference statements)
0
34
0
Order By: Relevance
“…A specific strength of the current study is that it includes the use of intensive longitudinal data, which allows us to examine dynamic within-subject changes. An additional advantage of this assessment method is that the weekly and daily diary questionnaires are less retrospective than regular measures and therefore might be less susceptible to recall bias [ 66 ]. Moreover, the current study will use multiple sources of information, as externalizing behavior problems will be reported by adolescents, parents, and teachers.…”
Section: Discussionmentioning
confidence: 99%
“…A specific strength of the current study is that it includes the use of intensive longitudinal data, which allows us to examine dynamic within-subject changes. An additional advantage of this assessment method is that the weekly and daily diary questionnaires are less retrospective than regular measures and therefore might be less susceptible to recall bias [ 66 ]. Moreover, the current study will use multiple sources of information, as externalizing behavior problems will be reported by adolescents, parents, and teachers.…”
Section: Discussionmentioning
confidence: 99%
“…As debate remains in relation to how to correctly quantify short-term BPV [ 24 , 49 ] our approach offers new alternatives that utilise the full power of ABPM that is often lost when using summary measures such as SD because it only reflects the dispersion of measurements around a single value (mean) not accounting for the order in which BP measurements were obtained [ 12 , 50 ]. As argued by Bamberger et al there are a large and increasing variety of mathematical equations available which allow us to test specific hypotheses about, and estimate parameters of, growth or change (BP) with varying purposes such as summarizing the shape of change across a sample or determining patterns in variability [ 51 ]. Despite this however, Diehl et al suggests that summary measures and multilevel models described here are two of the most common techniques used specifically for exploring BP changes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants will complete a range of self-report measures and a clinical interview at baseline (T0), post treatment (T1), and at follow-up (T2), 3-months after the T1 assessment, with an assessor who will be blind to participants’ allocation status. Clinical effect sizes will be estimated using two approaches, at the group level for a range of clinical outcomes by comparing change from pre to post treatment and at the individual level for the two primary outcomes—insight into mental disorder and use of adaptive coping skills—using intensive longitudinal methods (ILM) [ 7 , 8 ]. Findings from two large treatment evaluations, the PEPS trial [ 9 ] and Ministry of Justice’s evaluation of the prison-based Core Sex Offender Treatment Programme [ 10 ], demonstrated that psychological therapies have the potential to cause harm to patients, a concept which has received little attention until recently.…”
Section: Methodsmentioning
confidence: 99%
“…Following an intensive longitudinal methods (ILM) approach [ 7 , 8 ], the BIS and CSQ will be administered to all participants each week during the 12-week study treatment phase. Members of the local health care team will administer these weekly measures and as such they will not be blind to participants’ treatment allocation status.…”
Section: Methodsmentioning
confidence: 99%